Conjunctival flora in Behcet patients - Gunduz, Abuzer; Gunduz, Ayten; Cumurcu, Tongabay; Seyrek, Adnan (Canadian Ophthal Soc, 2008)
Background: To determine the difference in conjunctival flora in Behcet patients compared with the normal population. Methods: This study was carried out on a study group of 50 patients in the inactive period of Behcet's disease and a control group of 50 age- and sex-matched healthy subjects with no systemic or ocular disease. A swab was taken from the lower fornix using a sterile swab and inoculated into bloody eosin methylene blue, chocolate, and Sabouraud dextrose agar media. Results: The mean age was 36.04 (SD 2.16) years for the Behcet group and 35.64 (SD 1.96) years for the control group. Bacterial growth was observed in 92% (n = 46) of the Behcet group and 56% (n = 29) of the control group. The Behcet group results were Staphylococcus oureus in 12 (24%), coagulase negative staphylococci (CNS) in 32 (64%), Moraxello spp in 8 (16%), Streptococcus spp in 8 (16%), Bacillus spp in 4 (8%), Neisseria spp in 4 (8%), Candida spp in 3 (6%), and Haemophilus spp in 1 (2%). In the control group, the results were S. aureus in 2 (4%), CNS in 24 (48%), Moraxella spp in 2 (4%), Streptococcus spp in 1 (2%), Bacillus spp in 3 (6%), Neisseria spp in 3 (6%), and Candida spp in 1 (2%).
25th Congress of the European-Society-of-Cataract-and-Refractive-Surgery -- SEP 08-12, 2007 -- Stockholm, SWEDEN
Keywords: Behcet's disease; conjunctival flora; ocular infection